Innovative Wheelchair Design to Reduce Health Issues among Nurses During Patient Transfer - Puspitasari, Nia Budi; Rusnaldy; Ismail, Rifky; Prastawa, Heru (International Journal of Industrial Engineering and Management, 2025)
Nurses have the risk of experiencing work-related musculoskeletal disorders and also several other health issues due to patient-handling activities, such as lifting, moving, and repositioning. This research aims to design a wheelchair that helps nurses reduce the risk of injury when carrying out patient transfer activities and assists patients during their hospital treatment. The study integrates the Kano Model with Quality Function Deployment and tests the transfer wheelchair design using static load analysis simulation using the Fusion 360 program with 80kg patient loading. The research involved 188 respondents, including nurses and patients, and discussions were also held with doctors to gather user needs in the design of transfer wheelchairs. The three most significant values for wheelchair design priority are transfer wheelchairs made of strong materials, which facilitate the transfer process from and to the wheelchair, and transfer wheelchairs that are comfortable to use. The design of this transfer wheelchair has been tailored to the anthropometry of the Indonesian population and the spatial constraints of hospital beds, bathroom doors, and toilets. Article history: Received (December 22, 2024); Revised (June 5, 2025); Accepted (June 13, 2025); Published online (August 1, 2025)